PENGARUH DOSIS ECOENZYME TERHADAP BERAT BUAH OKRA (Abelmoschus esculentus) SEBAGAI SUMBER BELAJAR BIOLOGI MATERI PERTUMBUHAN DAN PERKEMBANGAN - Mayang Aprilia; HRA Mulyani; Agus Sujarwanta (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2026)
The objectives of this study were 1) to analyze the effect of variations in ecoenzyme dosage on okra plant production, 2) to analyze the ecoenzyme dosage that provides the best effect on okra plant production, 3) to analyze biology learning resources in the form of posters that are suitable for use by students based on the research results. This type of research is quantitative research using a Completely Randomized Design (CRD). This study consisted of 4 treatments and 4 replications. P1 = ecoenzyme 10 ml/L water, P2 = ecoenzyme 20 ml/L water, P3 = ecoenzyme 30 ml/L water, and P4 = ecoenzyme 40 ml/L water. The parameters observed included the number of okra fruits and the weight of okra fruits. Data were analyzed using normality tests, homogeneity tests, hypothesis tests, and BNJ. Based on the results of the study, the ecoenzyme dosage had a significant effect on okra plant production. The results of the hypothesis test showed that there were significant differences between treatments, and the results of the BNJ test showed that the P4 treatment had the best effect on okra plant production. Based on the analysis of learning resource validation, material expert validation showed a percentage of 80% and design expert validation showed a percentage of 88%, which means it has very valid qualifications so it is suitable for use as a biology learning resource in high school.